2019
DOI: 10.1080/20009666.2019.1583535
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B cell lymphoma primarily presenting as acute liver failure in a surviving patient

Abstract: Acute liver failure (ALF) is a relatively rare presentation of non-Hodgkin lymphoma, often found only during postmortem examination in patients. We treated a 33-year-old woman with prominent jaundice who was diagnosed with diffuse large B-cell lymphoma presenting as ALF. We could not perform liver biopsy during the critical phase because of coagulopathy, but gastric biopsy showed the infiltration of lymphoma cells. The patient was successfully treated with rituximab and chemotherapy and she survived. Malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Of note, ALF due to diffuse large B-cell lymphoma is reported to account for only 0.26% (5/1910) [1]; to date, only ten cases of ALF due to diffuse large B-cell lymphoma have been reported (Table 1) [6][7][8][9][10][11][12][13][14][15], with the time to death following admission in six reported cases being 5 days [12,13], 8 days [7,9], 14 days [14], and 19 days [6], in contrast to only 3 days in the present case. It has been reported that the deaths were caused by multi-organ failure involving cardiovascular collapse, acute lung injury, and renal failure, in addition to hepatic failure [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, ALF due to diffuse large B-cell lymphoma is reported to account for only 0.26% (5/1910) [1]; to date, only ten cases of ALF due to diffuse large B-cell lymphoma have been reported (Table 1) [6][7][8][9][10][11][12][13][14][15], with the time to death following admission in six reported cases being 5 days [12,13], 8 days [7,9], 14 days [14], and 19 days [6], in contrast to only 3 days in the present case. It has been reported that the deaths were caused by multi-organ failure involving cardiovascular collapse, acute lung injury, and renal failure, in addition to hepatic failure [5].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a few case reports showing that long-term survival could be achieved with chemotherapy in patients with ALF [8,11,15] and that the diagnosis of ALF is facilitated by liver biopsy, bone marrow biopsy, and gastric biopsy (Table 1), Rich et al highlighted the importance of early tissue sampling through liver biopsy [1], suggesting that early diagnosis by biopsy and treatment are crucial for survival in patients with ALF. However, liver biopsy should be carefully considered in ALF patients depending on their risk of complications, which may have been increased with coagulopathy and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, hematologic malignancies cannot be ignored, especially lymphoma. Hepatic infiltration of tumor cells can be observed in 15%-22% of hematological malignancies[ 15 ], rarely leading to significant liver dysfunction[ 16 - 20 ], which usually occurs in the terminal stage of the disease[ 16 , 17 , 21 , 22 ] and is closely related to high mortality (67%-100%)[ 16 ]. Although rare, some case reports have described this course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, earlier diagnosis and treatment should be the primary goal. A search of the literature found five cases of survival in patients with ALF associated with extranodal DLBCL [16][17][18][19][20]. All five of these patients received a variation of standard therapy based off the R-CHOP regimen, but specific treatment differed significantly from one patient to the next.…”
Section: Discussionmentioning
confidence: 99%